Pengaruh Gaya Hidup dan Tingkat Pendapatan terhadap Perilaku Konsumsi Islami pada New Normal (Studi Kasus Masyarakat Muslim Usia Produktif di Surabaya) - Fajirin, Fauzan Bahamarianto; Indrarini, Rachma (Universitas Negeri Surabaya, 2021)
In the teachings of Islam, consumption behavior is based on the Al-Quran and Hadith where in consumption, satisfaction is not number one, but maslahah (benefit) must be prioritized in carrying out consumption activities. Many factors can influence Islamic consumption behavior, one of which is lifestyle and income level. Situations and conditions during the